CSR Disclosure towards Return On Assets: Study from Indonesia Banking Companies - Satya Kustamaputra Wicaksono; Astrie Krisnawati (Postgraduate Program Merdeka University, 2021)
Corporate Social Responsibility is a concept of how an organization have the responsibility toward their stakeholders, including their employees, consumers, shareholders, social, and the environment. This study investigates the influence of Corporate Social Responsibility Disclosure towards Return On Assets of banking firms registered in the Indonesia Stock Exchange from 2017-2020. Based on the purposive sampling carried out by the researchers, there are 9 banking companies being observed in the study. The data is analysed using the Data Panel Regression Analysis. The result reveals a significance and negative influence of Corporate Social Responsibility Disclosure towards Return On Assets. These findings can assist banking companies to disclosure their CSR actions in the future, because not only it will fulfil the regulation established by the government, but also create positive image of the companies in the public’s perception.